Optimization of InAs/GaAs submonolayer quantum dots grown on GaAs(001) with a (2×4) surface reconstruction for infrared photodetectors - Zeidan, Ahmad Al (2023)
In the present work, we have investigated the application of InAs/GaAs submonolayer quantum dots (SML-QDs) as a new type of nanostructures for mid-infrared detection, which are slowly replacing conventional Stranski-Krastanov quantum dots (SK-QDs) in some specific applications. Photoluminescence (PL) and cross-seccional scanning tunneling microscopy (X-STM) were used to investigate and optimize their growth conditions. Subsequently, several infrared photodetectors based on InAs/GaAs SML-QDs were grown by molecular beam epitaxy, processed in a clean room by photolithography, and finally tested extensively to determine how their performance improves when grown with a (2×4) surface reconstruction, achieved either at low temperatures (490 C) with a low As flux (8.0 E-8 Torr) or at high temperatures (528 C) with a high As flux (7.0 E-7 Torr). Since one drawback of SK-QDs is their low surface densitywhich is roughly 10-100 times lower than that of SML-QDswe also propose a way to further increase their density using the seed concept. By pre-depositing InAlAs quantum dots, which naturally have a density 10 times higher than InAs SK-QDs, the strain field generated by the first layer of InAlAs QDs can serve as a seed to nucleate the second layer of InAs QDs, which helps to increase their density when the separation is kept small.